Evaluation of Landsat-8 OLI and Sentinel-2 MSI images for estimating the ecological quality of port waters - Maurizio Pieri (European Journal of Remote Sensing, 2021)
Recent research has demonstrated that the TRophic IndeX (TRIX) is informative on the ecological quality of Mediterranean port waters and can be estimated by the processing of multispectral observations collected in situ. The current study investigates the alternative use of multispectral data acquired by medium-high spatial resolution optical satellite sensors, i.e. the Landsat-8 (L8) Operational Land Imager (OLI) and the Sentinel-2 (S2) MultiSpectral Instrument (MSI). The study analyzes the impact of the main factors influencing TRIX estimation using datasets collected in several Mediterranean ports and particularly in those of Civitavecchia and Viareggio (Central Italy). The experimental results indicate that the spectral configurations of OLI and MSI have a marginal impact on TRIX estimation, while major effects are caused by the different spatial and temporal features of the two sensors. The enhanced spatial properties of MSI are important particularly in the smaller port of Viareggio; the higher acquisition frequency of this sensor brings significant advantages for operational monitoring applications. Overall, the accuracy of TRIX estimation based on in situ spectral measurements is reduced significantly by the use of OLI images and only marginally by that of MSI images. Both image types represent an advancement for the operational monitoring of port waters.